Cartoon Film Media in Improving Narrative Writing Ability Of 11th Grade Science Students Of SMAN Situraja - Enjang Kartiwa, Cece (STIT Buntet Pesantren Cirebon, 2022)
The objectives of the research are: (1) to find out whether the students’ skill in writing narrative texts can be improved by using cartoon films. (2) to find out the effectiveness of the teaching and learning process when cartoon films are used in teaching writing narrative texts. The researcher collected the data using qualitative and quantitative data. The improvement of students’ writing skill includes: (1) having an abundance of vocabulary; (2) using correct capitalizations and spelling; (3) making sentences grammatically; (4) developing their ideas into coherent paragraphs. The effectiveness of using cartoon films shown in: (1) motivating students to write; (2) making the lesson more clearly (3) increasing their interest; (4) increasing their attention. The students’ score in pre-test was 61.77, post-test 1 in cycle 1 was 70.6, and post-test 2 in cycle 2 was 74.90. It can be concluded that the use of cartoon films can improve students’ skill in writing narrative text.